PENINGKATAN PERKEMBANGAN MOTORIK KASAR DI TAMAN KANAK-KANAK GEMBALA BAIK PONTIANAK - Rita, Helena; Ali, Muhamad; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The purpose of this research is to know the improvement of gross motor development after using traditional game of coconut shell in children aged 5-6 years in Kindergarten Good Shepherd Pontianak. in general can be drawn a conclusion that: 1) Learning planning using traditional games of coconut shell to improve gross motor in children aged 5-6 years is categorized as "good", 2) Implementation of learning using traditional game of coconut shell to improve motor coarse in child ages 5-6 years are categorized as "good", 3) Increased motor gross in children aged 5-6 years after using traditional game of coconut shell stilts include: a) The child performs body movement by maintaining balance. that can fly increased by 85%, b) Children do foot coordination in walking so do not fall often increased by 80%, c) Children move actively so as not to exceed the time limit increased 80%.Â Keywords: Locomotor, Coconut Shell EgrangÂ